A serious game design and development : education game for mobile devices - Tang, Chun Boon (Nanyang Technological University, 2020)
Educational games provide an interesting concept of merging work and play together. As mobile games continue to rise in terms of its popularity, it is a great opportunity for educational games to be part of that same market as well. This project aims to explore the possibilities of educational games on mobile platform and introducing a way for the tutor to be part of the student’s learning process. In this project, the focus will be on researching into game design and learning process and applying it by developing a functional system. The entire infrastructure will consist of a game on mobile platform for the students, as well as an interactive web interface for tutors.